Microstructure and Mechanical Properties of Wrought and Additive Manufactured Ti-6Al-4 V Cylindrical Bars. (2015) - Shunmugavel, Manikandakumar; Polishetty, Ashwin; Littlefair, Guy
Abstract: Titanium alloys are widely used in various engineering design application due to its superior material properties. The traditional manufacturing of titanium products is always difficult, time consuming, high material wastage and manufacturing costs. Selective laser melting (SLM), an additive manufacturing technology has widely gained attention due to its capability to produce near net shape components with less production time. In this technical paper, microstructure, chemical composition, tensile properties and hardness are studied for the wrought and additive manufactured SLM cylindrical bar. Microstructure, mechanical properties and hardness were studied in both the longitudinal and transverse directions of the bar to study the effect of orientation. It was found that additive manufactured bar have higher yield strength, ultimate tensile strength and hardness than the wrought bar. For both conventional and SLM test samples, the yield strength, ultimate tensile strength and hardness was found to be high in the transverse direction. The difference in the properties can be attributed to the difference in microstructure as a result of processing conditions. The tensile fracture area was quantified by careful examination of the fracture surfaces in the scanning electron microscope.